Staff development for piloting the technology education curriculum for primary and lower secondary schools in the CARICOM : report on the conduct of workshops in eight CARICOM states - Gift, Edrick H. (CCS GeorgetownGY, 2003)
Reports on the preparations for the actual piloting of the technology education curriculum.